1998
DOI: 10.1210/jcem.83.5.4839
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Sodium Iodide Symporter Gene Expression in Extrathyroidal Tissues and Cloning of Its Complementary Deoxyribonucleic Acids from Salivary Gland, Mammary Gland, and Gastric Mucosa

Abstract: The ability to concentrate iodide is a fundamental property of normally functioning thyroid tissue and represents the first step in the production of thyroid hormones. Iodide uptake has been demonstrated in various extrathyroidal tissues, including salivary gland, gastric mucosa, and lactating mammary gland. Recently, cloning and molecular characterization of the human sodium iodide symporter (hNIS) have been reported; however, the patterns of hNIS gene expression in human tissues have remained unidentified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
2
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(117 citation statements)
references
References 23 publications
4
106
2
5
Order By: Relevance
“…Spitzweg et al (32) reported that breast cancer and thyroid tissue express sodium iodide symporter genes; and Kilbane et al (33) demonstrated that breast cancer tissue iodine content was significantly lower compared to that in normal breast tissue or fibroadenoma, suggesting an iodine uptake pathology in breast cancer. Previous epidemiological studies demonstrated an inverse correlation between iodine intake and breast cancer incidence (12,34).…”
Section: Discussionmentioning
confidence: 99%
“…Spitzweg et al (32) reported that breast cancer and thyroid tissue express sodium iodide symporter genes; and Kilbane et al (33) demonstrated that breast cancer tissue iodine content was significantly lower compared to that in normal breast tissue or fibroadenoma, suggesting an iodine uptake pathology in breast cancer. Previous epidemiological studies demonstrated an inverse correlation between iodine intake and breast cancer incidence (12,34).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Endogenous expression of the hNIS gene has been found primarily in thyroid tissue but also, to a much lower extent, in other secretory and exocrine tissues. 7 These observations indicate that, following thyroid blockade, it may be possible to deliver Na 131 I to transfected, hNIS-expressing, tumor cells with minimal uptake of radioactivity in normal tissues.…”
mentioning
confidence: 82%
“…8 Endogenous NIS expression has not been found in lung cancer and it is not present in normal lung tissue. 9,13 Transfection of a variety of tumors including melanoma, colon carcinoma, ovarian adenocarcinoma, lung cancer, 10,11 and prostate cancer 12 with an NIS -expressing vector results in increased radioiodide uptake. However, rapid radioiodide efflux from these transfected cells may limit the antitumor efficacy of this therapeutic strategy.…”
mentioning
confidence: 99%